Kajian Kriminologis Penanggulangan Tindak Pidana Penganiayaan (Studi Pada Polresta Pulau Ambon dan Pulau-Pulau Lease) - Christy Moren Manduapessy; Deassy Jacomina Anthoneta Hehanussa; Julianus Edwin Latupeirissa (PATTIMURA Law Study Review, 2023)
The crime of assault is an act committed by someone intentionally causing pain or injury to another person. In Maluku Province, especially Ambon City, criminal acts of abuse investigated by the P. Ambon and P. P. Lease Police in the last 3 years have increased, according to Article 351 of the Criminal Code. This research aims to find out whether criminological aspects are taken into account in dealing with criminal acts of abuse and how criminal acts of abuse carried out by the P.Ambon and P.P Lease Police are handled. The research method used empirical juridical research methods Research Locations P. Ambon and P.P Lease Police, Nusaniswe Police, Teluk Ambon Police and Sirimau Police, Sample, Population, Respondents, Data sources used are primary data and secondary data. Material collection techniques through observation, interviews and quantitative analysis of legal materials. Based on the results of research and discussion, in Maluku Province, especially Ambon City, it is handled by the P. Ambon Police and P. P. Lease, namely criminal acts of abuse. The phenomenon that occurred at Nusaniwe Police, Teluk Ambon Police and Sirimau Police has increased in the last three years. Law enforcement of criminal acts of abuse at the P. Ambon and P. P. Lease police stations lacks incomplete evidence, there is a lack of public understanding, especially witnesses who see and know about criminal acts of abuse, often do not want to be witnesses in the investigation process until the trial stage and victims do not know who the perpetrators are. Committing criminal acts of abuse. Efforts to overcome criminal acts of abuse can be carried out using three measures, namely Pre-emptive Efforts, Preventive Efforts and Repressive Efforts. Pre-emptive efforts made by the police to instill good norms. Preventive efforts through coaching, education and community awareness. Repressive efforts were carried out by rehabilitation.